Impact of the armed conflict on victims and support workers' mental health in Soacha, Colombia - Sandra Elizabeth Piñeros; Nathaly Garzón; Zulma Consuelo Urrego; Nikki Coghill; Daniel Samacá; Javier Hernando Eslava (Biomédica: revista del Instituto Nacional de Salud)
Introduction. In the Colombian context, research on victims of armed conflict has demonstrated that exposure to violence impacts different aspects of their lives and represents a challenge for their support workers. Objective. To explore perceptions, beliefs, and knowledge about mental health and support sources among victims of forced migration –due to the internal armed conflict– and their support workers in Soacha, Colombia. Materials and methods. We conducted a qualitative exploratory study. Data were collected from December 2018 to March 2019 using separate focus groups of victims and workers. Thematic content analysis established five deductive categories: perceptions of mental health; the impact of forced displacement and its relationship with mental health; knowledge or perception of institutional support; community networks; and knowledge or perception of the state measures concerning care, assistance, and reparation. We also included some inductive categories that emerged from the analysis. Results. Victims demonstrated deteriorated mental health, expressed by emotional, cognitive, and behavioural disturbances. Many of these conducts were exacerbated by the traumatic stress of displacement and exposure to other forms of violence, in addition to social and material deprivation. Emotional avoidance and active search for self-improvement emerged as coping mechanisms used by the victims. Workers experienced high levels of stress assisting trauma victims, and they also needed support for their mental health. Conclusions. The findings showed complex and mainly negative impacts on mental health in both groups. Interventions should aim to address poor mental health and strengthen cultural identity and support networks for victims.